EFFECT OF IRRIGATION FREQUENCY ON THE YIELD AND VEGETATIVE GROWTH OF TWO OLIVE CULTIVARS (CVS . KORONEIKI AND PICHOLINE) I N ARID LANDS - A. Sghaier; R. B. Ayed; N. Sghaier; K. Naggaz; M. Ouessar; D. Boujnah (Journal of Animal and Plant Sciences, 2019)
A field experiment was carried out to investigate the effect of tree irrigation frequency on the vegetative growth and yield of two introduced olive cultivars (Olea europaea L. cvs. Koroneiki and Picholine). The trials took place in 2014. There were four different irrigation treatments, which were irrigating every other day (T0), every 4 days (T1), every 8 days (T2) and scheduling irrigation according to farmer experience (FM). Vegetative tree responses, such as shoot growth, basal diameter and number of leaves, were evaluated. Olive fruit morphological characteristics (olive length, olive diameter and weight) and yields were also determined. The vegetative growth of both cultivars was directly associated with water availability throughout the experiment. The Picholine cultivar had better growth-related parameters than Koroneiki. However, Picholine did not have an autumnal growth period. Furthermore, it only produced a significant yield under well irrigated conditions. Koroneiki tree yields were higher than Picholine yields for all irrigation frequencies. Irrigation treatment T2 had the most water depressive effect on the Koroneiki cultivar because a 50% reduction in the water supply reduced the yield by 43%. The olive characteristics of both cultivars were not affected by watering frequency.
Keywords: Shoot growth; fruit characteristics; heat stress; water stress